Analysis of deviations and delays in aid disbursements - Matthew Odedokun (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
The study seeks to identify donor-specific factors that cause donors to delay aid disbursement, and to apply a double standard in dealing with the non-compliance of a recipient with regard to aid conditionalities, a practice that promotes uncertainty in the receipt of aid. Annual panel data over 1970-2000 for the 22 members of OECD's DAC donor group are employed in the empirical study. Our findings suggest that the proportion of pledged aid being disbursed, which shows an increasing trend, is positively affected by the extent to which aid is procurement-tied and by the size of the donor government's expenditure in relation to GDP. On the other hand, the proportion of aid commitments being disbursed, which appears lower for the G7 countries, is negatively influenced by factors such as abundant donor generosity, the predominance of grants in total aid, the specific targeting of aid to lower-income recipients, high growth in donor economy, as well as high level of checks and balances, and polarization between the executive and legislative branches of government in the donor country.
Keywords: F35; 330; aid disbursement; aid commitment; donors; recipients; conditionality; instability; uncertainty; Entwicklungshilfekonditionen; OECD-Staaten; Entwicklungsländer